Pengaruh Investment Opportunity Set Terhadap Kualitas Laba Dengan Konservatisme Sebagai Variabel Moderating - Narita Narita; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to examine the factors that affect earnings quality, namely investment opportunity sets that are moderated by conservatism in manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The selection of a sample of 50 companies uses a purposive sampling method. This study uses the MRA (Moderated Regression Analysis) analysis technique for testing moderating variables by comparing the coefficient R² before and after the moderating variable. The results of this study indicate that the investment opportunity set does not significant affect on earnings quality. Conservatism is able to moderate the relationship between investment opportunity set and earnings quality, which is to strengthen the relationship between these variables. This is indicated by an increase in the coefficient value of R².